Investigation of the Exercise Dependence of Athletes Doing Kickboxing, Taekwondo, and Muay Thai - Orhan, Serdar; Yucel, Ali Serdar; Sadeq, Bootan Jawhar; Orhan, Ebru (Mdpi, 2019)
Debates about the conditions in which the frequency and intensity principles of regular exercise, depending on the fact that a sports background can be accepted as extremism, are still a controversial topic. The purpose of this research was to investigate the exercise dependence of athletes who practice Kickboxing, Taekwondo, and Muay Thai. The study included 141 athletes, consisting of 87 men and 54 women. The Exercise Dependence Scale-21 (EDS-21), composed of 21 items developed by Hausenblas and Downs and adapted into the Turkish version by Yeltepe and Ikizler, was applied to the athletes. As a result of the research, while athletes showed more sensitivity to the EDS (=71.41), this scale was also defined as symptomatic. It was found that five athletes (3.5%) were asymptomatic-nondependent, 117 athletes (83.0%) were symptomatic-nondependent, and 19 athletes (13.5%) were at risk for exercise dependence. It was determined that athletes were at risk for exercise dependence as follows: Eight athletes were doing Kickboxing, ten athletes were doing Taekwondo, and one athlete was doing Muay Thai. A significant difference was observed according to years of regular training and number of trainings per a day. Other variables presented no significant differences. It was possible to say that years of regular training could be effective in revealing exercise dependence.
Keywords: exercise dependence; symptomatic; asymptomatic; Kickboxing; Taekwondo; Muay Thai